Exploring Relationship between Home Environment and Study Habits of Pre-service Teachers of DIETs from Delhi - Rekha, Chiter (JOURNAL OF INDIAN EDUCATION, 2022)
The present study was an attempt to explore the relationship between home environment and study habits of pre-service teachers of DIETs from Delhi. The main objectives of this paper were to study the home environment and study habits of pre-service teachers and to study the relationship between their home environment and study habits. sample of 80 pre-service teachers was taken into consideration by using random sampling. The study habit inventory developed by M.N. Palsane and Anuradha Sharma, and home environment inventory developed by Karuna Shanker Mishra were used to measure the study habits and the home environment of pre-service teachers of DIETs from Delhi. Percentage (%), t-test and co-efficient of correlation were used by the investigator to analyse the data for testing the hypotheses and relationship between study habits and home environment of pre-service teachers. The investigator found no significant difference between home environment and study habits of male and female pre-service teachers of DIETs. Positive and significant relationships were found between the study habits and home environment of pre-service teachers.